If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2y = 18 Solving 3x + -2y = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 3x + -2y + 2y = 18 + 2y Combine like terms: -2y + 2y = 0 3x + 0 = 18 + 2y 3x = 18 + 2y Divide each side by '3'. x = 6 + 0.6666666667y Simplifying x = 6 + 0.6666666667y
| 13=10-z | | -6x^2-25x-25=0 | | 4t^2+33t+54=0 | | -13=-26 | | 50-4Q=2 | | 4(7-x)-40=2x-3(4+2x) | | 11x+x^2-28=0 | | 15x^2+4x-3=0 | | a+19=-82 | | 15=7+h+14 | | 8+f=30 | | s+31=14 | | -10-8y=7y | | 311=y-281 | | 68=p-41 | | 15=z+6 | | 0=.5+1.5x | | -7m+2m=3(2+m)+4(1-2m) | | y-34=43 | | y=44(2200)+2500 | | 18+n-7=44 | | x(7x-8)=15 | | 8-2r=-12 | | 24=k-2 | | 9r+15-10r=24 | | 37=z-3 | | -11+b=-11 | | 10a+101ab+10b^2= | | 144+g=78 | | 63=9a-27 | | r+7=-16 | | C^2-9= |